Silica extract from Malang beach sand via leaching and sol-gel methods - Sumari Sumari; Muhammad Roy Asrori; Yana Fajar Prakasa; Dinar Rachmadika Baharintasari; Aman Santoso (Institute of Advanced Engineering and Science, 2023)
Many silica minerals are found in beach sands. One of its beach sands is in Bajul Mati beach sand which contains high silica. The silica can be extracted using existing methods, but it is less environmentally friendly. In this research, the extracting process of silica from the sand of Bajul Mati beach (South of Java-Indonesia) has been carried out through a method that is low-cost and more environmentally friendly. The purpose of this study was to characterize extracted silica with instrumentation results and economic analysis. The method of extracting silica from beach sand was via leaching and sol-gel methods: i) leaching with 7M HCl,ii) the formation of clear sodium silicate solution (Na2O.SiO2),iii) sol-gel: sodium silicate solution titrated with oxalic acid (H2C2O4) 1 M until pH 6 was obtained and silicite Si(OH)4 was formed, and iv) characterization with X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and scanning electron microscopy (SEM) with economic analysis. The result showed that extracted silica has a cristobalite structure based on XRD analysis. The purity of silica (% Wt Si) reached 93.9% based on XRF analysis. FTIR analysis has identified silanol, siloxic, and siloxane groups. The SEM analysis shows that silica (SiO2) particles tend to form agglomerations about ∼1 μm. In addition, economic analysis results showed that this method will support implementation in the future, so silica has been produced by this developed method.